2013
DOI: 10.1088/0031-8949/88/06/065305
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the 4p5nlnl′ autoionizing states of Rb excited by electron impact

Abstract: Large scale configuration interaction calculations of energy levels, autoionization probabilities and electron-impact excitation cross sections of the autoionizing states 4p5nln′l′ (nl = 5s,4d,5p,4f; n′l′ = 4d,5s,5p,5d,5f,5g,6s,6p,6d,7s,7p) of Rb up to 19.6 eV were performed for the first time. The relativistic effects were taken into account in the Dirac–Fock–Slater approximation. The asymmetry parameters of the angular distribution of Auger electrons for a number of electron-impact excited states were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Our calculations for excitation of the autoionizing states of Cs and Rb [18] have shown that the alignment parameters A K depend strongly on the configuration and total angular momentum J, but are very similar for the total orbital L and spin S angular momenta. It is sufficient to calculate the factors C = 1 + ∑ K A K α K P K (cos θ) only for the 5p 5 nln'l' J states which are a good tool to estimate the change of ratios of the intensities of Auger lines in the case of J = 1 / 2 and J ≥ 3 / 2 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Our calculations for excitation of the autoionizing states of Cs and Rb [18] have shown that the alignment parameters A K depend strongly on the configuration and total angular momentum J, but are very similar for the total orbital L and spin S angular momenta. It is sufficient to calculate the factors C = 1 + ∑ K A K α K P K (cos θ) only for the 5p 5 nln'l' J states which are a good tool to estimate the change of ratios of the intensities of Auger lines in the case of J = 1 / 2 and J ≥ 3 / 2 .…”
Section: Resultsmentioning
confidence: 81%
“…In addition, A K = 0 for all J = 1 / 2 states of the excited atom. Therefore, intensity ratios of the J = 1 / 2 and J > 1 / 2 lines observed at 75° can differ significantly from the ratios obtained when we exclude the asymmetry of the angular distribution of ejected electrons (see details in [18] for the core-excited Rb).…”
Section: Methods Of Calculationsmentioning
confidence: 80%
“…However, the authors emphasized that there is little or no agreement between their experimental and calculated ejected-electron spectra that correspond to process (1). Meanwhile, as was shown in our recent studies of ejected-electron spectra of heavy alkalis Rb [17,18] and Cs [19], an accurate identification of the complex line structure may be feasible only if a certain minimum of data on processes (1) and (2) is available. These data are (i) experimental excitation thresholds and excitation dynamics of lines; (ii) calculated excitation energies, cross sections and decay rates of the states under study.…”
Section: Introductionmentioning
confidence: 98%
“…2 3 P 0,1,2 and 3 F 2,3,4 most low-lying atomic AIS.Meanwhile, according to our previous analysis of ejected-electron spectra of heavy rubidium[15], caesium[16] and…”
mentioning
confidence: 86%